Evaluation of the properties of AA7020 tubes generated by a heat treatment based hydroforming process - Reblitz, Jonas; Trân, Ricardo; Kräusel, Verena; Merklein, Marion (SheMet2023, 2023)
Energy efficiency and sustainability are getting more and more relevant in society and industry. Especially energy-intensive sectors offer a high potential for power savings. Thus, different lightweight strategies are applied in the automotive sector. In this context, high strength profile components are used as crash structures. As an example, these profiles are deployed to protect the battery of electrically powered vehicles. Therefore, high strength aluminum alloys of the 7xxx series are suitable for compensating the high battery weight partly. Compared to steel, this material is characterized by a high strength-to-weight ratio as well as an increased thermal conductivity. However, one challenge in forming high strength aluminum alloys is the limited formability at room temperature. For this purpose, heat treatment based process routes for tube hydroforming are investigated within this research work. By the combination of W-temper forming and hydroforming complex part geometries can be generated. A subsequent artificial ageing process realizes the required high strength of the profiles. Using AA7020 tubes, the properties of a demonstrator geometry are compared to the initial state T6 of the semi-finished parts. For this purpose, the wall thickness distribution and the grain structure are evaluated. Thereby, the influence of forming and heat treatment on the geometrical and microstructural properties is to be analyzed. For the evaluation of the achievable hardening of the aluminum alloy, the mechanical properties are investigated by tensile tests. This investigations provide an assessment of the process route under industry-related conditions.<br
Keywords: Heat Treatment; Hydroforming; Tubes